Photolytic release of butyric acid from oxygen and nitrogen based heteroaromatic cages - Soares, Ana M. S. (2012)
In order to develop butyric acid photoactive prodrugs, new heteroaromatic conjugates based on oxygen and nitrogen were synthesised and evaluated under irradiation at 254, 300, 350 and 419 nm. Light triggered uncaging of butyric acid from the corresponding heterocyclic cages was achieved with complete release of the drug in short times. Naphtho[2,3-d]oxazole, naphtho[1,2-d]oxazole, 3-oxo-3H-benzo[f]benzopyran, 2-oxo-2H- benzo[h]benzopyran and 6-oxo-6H-benzopyrano[6,7-d]oxazole conjugates were readily photolyzed, the best results were obtained for naphtho-oxazoles at 254 and 300 nm, and for 3-oxo-3H-benzo[f]benzopyran, 2-oxo-2H-benzo[h]benzopyran and 2-methyl-6-oxo-6H-benzopyrano[6,7-d]oxazole at 350 nm. The 3-oxo-3H-benzo[f]benzopyran also afforded the best results at 419 nm. The photophysical processes involved were further elucidated by the use of time-resolved fluorescence techniques.